Aluminum-based composite material and preparation method and application thereof

By setting a ta-C film on the microarc oxide layer, the problem of insufficient hardness and wear resistance of the existing aluminum alloy surface oxide layer is solved, and the high hardness, high bonding strength and good corrosion resistance of the material are achieved, which is suitable for high-speed and heavy-load conditions.

CN119663396AActive Publication Date: 2025-03-21CHONGQING ZHONGGUANG CONSTR COATING TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411687737.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-21
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The surface oxide layer of the aluminum alloy formed by the existing microarc oxidation method has a large surface roughness, low hardness, poor wear resistance, and high porosity of the oxide film layer, resulting in corrosion and wear problems.

Method used

A ta-C film is provided on the microarc oxide layer. The ta-C film consists of a chromium layer, a tungsten carbide layer and a carbon layer in sequence. It is prepared by physical vapor deposition technology to form a suitable hardness gradient to improve binding force and corrosion resistance.

Benefits of technology

It significantly improves the hardness, wear resistance and corrosion resistance of the material, enhances the bonding force between the ta-C film and the microarc oxide layer, improves the toughness and corrosion resistance of the composite material, and is suitable for high-speed and heavy-load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663396A_ABST
    Figure CN119663396A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum-based composite material and a preparation method and application thereof. The aluminum-based composite material comprises a base material, wherein the base material is made of aluminum or aluminum alloy; the micro-arc oxidation layer is arranged on the surface of the base material, and the micro-arc oxidation layer is prepared through a micro-arc oxidation method; the ta-C thin film is arranged on the surface of the micro-arc oxidation layer, the ta-C thin film is prepared through a physical vapor deposition technology, and the ta-C thin film comprises a chromium layer, a tungsten carbide layer and a carbon layer which are sequentially arranged in the direction away from the micro-arc oxidation layer. The aluminum-based composite material has high hardness, wear resistance and corrosion resistance, is not prone to deformation and is suitable for being applied to high-speed and heavy-load working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy surface coatings, and specifically relates to an aluminum-based composite material and a preparation method and application thereof. Background Art

[0002] In recent years, with the rapid economic growth, the demand for various materials has been increasing day by day, especially lightweight, durable and energy-saving materials. These demands have increased the output of aluminum alloys year by year. Since 1991, the total consumption of aluminum materials in the world has been 18.744 million tons, while my country's total aluminum consumption has been 8.68 million tons. By 2000, the total consumption of aluminum materials in the world has increased to 24.7798 million tons, with a ten-year growth rate of 32%; while my country's total aluminum consumption has increased to 3.5327 million tons, a growth rate of three times. Aluminum is one of the most commonly used light metals and the second most abundant element in the earth's crust. The density of pure aluminum is 2.7g / cm 3 , with a small specific gravity (about 2.7), which is 35% of iron and 30% of copper. Aluminum alloy is also the most widely used type of non-ferrous metal structural material in industry. It is an engineering alloy composed of aluminum as the base metal element and alloy elements and impurities. It has the characteristics of lightness, low cost, excellent corrosion resistance, high thermal conductivity and recyclability, which makes it have good formability, weldability and machinability, and is widely used in automotive, aerospace and other industrial fields.

[0003] However, as a structural material, aluminum alloy has the disadvantages of being soft, poor in wear resistance, poor in corrosion resistance under special environments, and poor in high temperature resistance. Moreover, although aluminum alloy can spontaneously form an A12O3 film in the air, the film is very thin and has many defects, and cannot effectively protect the substrate.

[0004] Therefore, researchers usually use surface modification methods such as micro-arc oxidation, anodizing, chemical oxidation, plasma spraying, and vapor deposition to modify the surface of aluminum and aluminum alloys. Among them, micro-arc oxidation technology is a technology for in-situ growth of ceramic layers on the surface, which has the advantages of high production efficiency, stable process, and good repeatability. However, the micro-arc oxidation layer formed by the existing micro-arc oxidation method has a large surface roughness, low hardness, poor wear resistance, and the oxide film layer has a large porosity. These problems will make it easier for corrosive media to penetrate the film layer and cause corrosion, and its surface wear rate is high. Summary of the invention

[0005] In order to solve all or part of the above technical problems, the present invention provides the following technical solutions:

[0006] One of the purposes of the present invention is to provide an aluminum-based composite material, comprising:

[0007] A substrate, wherein the material of the substrate includes aluminum or aluminum alloy;

[0008] A micro-arc oxidation layer is disposed on the surface of the substrate, and the micro-arc oxidation layer is prepared by a micro-arc oxidation method;

[0009] A ta-C film is arranged on the surface of the micro-arc oxidation layer. The ta-C film is made by physical vapor deposition technology and comprises a chromium layer, a tungsten carbide layer and a carbon layer which are arranged in sequence in a direction away from the micro-arc oxidation layer.

[0010] The present invention arranges the ta-C film on the micro-arc oxidation layer, which can significantly improve the hardness, wear resistance and corrosion resistance of the material. The chromium layer, tungsten carbide layer and carbon layer arranged in sequence in the ta-C film can make the ta-C film as a whole have a suitable hardness gradient. This reasonable hardness transition can increase the bonding force between the three layers of the ta-C film, as well as increase the bonding force between the ta-C film as a whole and the micro-arc oxidation layer, thereby improving the toughness of the composite material. The ta-C film can close the tiny holes on the surface of the micro-arc oxidation layer, prevent the corrosive medium from entering through the holes and causing the ceramic film to fall off, and increase the corrosion resistance of the material. In addition, the aluminum-based composite material has good anti-deformation performance, so that the composite material is not easy to deform and fail under high-speed and heavy-load conditions.

[0011] In some embodiments, the thickness ratio of the micro-arc oxidation layer to the ta-C film is 15-25:2.9-5.

[0012] In some embodiments, the thickness ratio of the chromium layer, the tungsten carbide layer and the carbon layer is 600N1000:100-500:

[0013] 1200N3500.

[0014] In some embodiments, the thickness of the micro-arc oxidation layer is 15-25 μm, the thickness of the ta-C film is 2.9-5 μm, wherein the thickness of the chromium layer is 600-1000 nm, the thickness of the tungsten carbide layer is 100-500 nm, and the thickness of the carbon layer is 1.2N3.5 μm.

[0015] In some embodiments, the carbon layer is a hydrogen-free carbon layer. Compared with a conventional carbon layer, the hydrogen-free carbon layer has better toughness.

[0016] In some embodiments, the material of the micro-arc oxidation layer includes alumina ceramics, such as alumina ceramics with grades of 2014, 2024, 5052, and 5083.

[0017] A second object of the present invention is to provide a method for preparing an aluminum-based composite material, comprising:

[0018] Providing a substrate, wherein the material of the substrate includes aluminum or an aluminum alloy;

[0019] Forming a micro-arc oxidation layer on the surface of the substrate by a micro-arc oxidation method;

[0020] A chromium layer, a tungsten carbide layer and a carbon layer are sequentially deposited on the surface of the micro-arc oxidation layer by adopting a physical vapor deposition technology to form a ta-C film, thereby obtaining an aluminum-based composite material.

[0021] In some embodiments, the micro-arc oxidation method specifically includes: using the substrate as an anode, placing it together with a cathode in an electrolyte containing 20 to 40 g / L of a silicate (for example, an alkaline silicate), and performing micro-arc oxidation treatment in a constant voltage mode; wherein the positive voltage is 500 to 550 V, the negative voltage is 30 to 100 V, the frequency is 400 to 600 Hz, and the duty cycle is 10 to 30%.

[0022] In some embodiments, the micro-arc oxidation treatment time is 10 to 50 minutes.

[0023] In some embodiments, the temperature of the electrolyte is 20-70°C.

[0024] In some embodiments, the alkaline silicate includes one or a combination of sodium silicate, sodium metasilicate, potassium silicate, iron silicate, magnesium silicate, and calcium silicate.

[0025] In some embodiments, the electrolyte further includes 2-12 g / L of an alkaline pH regulator for adjusting the pH value of the electrolyte to be weakly alkaline. The alkaline pH regulator includes, for example, sodium hydroxide and potassium hydroxide, but is not limited thereto.

[0026] In some embodiments, the electrolyte further includes 2-15 g / L of a colorant for coloring the surface of the aluminum-based composite material. The colorant includes, for example, one or a combination of sodium metavanadate, copper sulfate, and copper carbonate, but is not limited thereto.

[0027] In some embodiments, the electrolyte further includes 2-8 g / L of a surfactant, such as sodium dodecyl sulfate and / or sodium fluoride, but is not limited thereto.

[0028] In some embodiments, the solvent of the electrolyte includes water.

[0029] In some embodiments, the cathode is made of stainless steel.

[0030] In some embodiments, the preparation method further includes, before depositing the ta-C film, etching and cleaning the substrate containing the micro-arc oxidation layer, the etching and cleaning comprising: placing the substrate containing the micro-arc oxidation layer in a physical vapor deposition reaction chamber, etching and cleaning under the conditions of vacuum degree ≤2×10-3Pa, temperature of 130~160°C, and bias voltage of -700~-900V, and then depositing the ta-C film.

[0031] In some embodiments, the physical vapor deposition technology specifically includes: in an argon atmosphere with a gas pressure less than or equal to 1 Pa, a chromium target and a tungsten carbide target are used to deposit a chromium layer and a tungsten carbide layer respectively, wherein the deposition time of the chromium layer is 60 to 190 minutes, and the deposition time of the tungsten carbide layer is 350 to 440 minutes.

[0032] In some embodiments, the physical vapor deposition technology specifically includes: after the tungsten carbide layer is completed, the pressure of the argon atmosphere is adjusted to be less than or equal to 1.5 Pa and the vacuum degree is less than or equal to 3×10 -3 Pa, and adjust the temperature to 30-50°C, the multi-arc current to 100-115A, the bias voltage to -750--900V, and use a graphite target for deposition for 800-1500min to form the carbon layer on the tungsten carbide layer. The deposited carbon layer is a hydrogen-free carbon layer.

[0033] In some embodiments, the preparation method further comprises: before micro-arc oxidation of the substrate, pre-treating the substrate to remove surface dirt. For example, the pre-treatment comprises grinding with 300# to 2000# sandpaper.

[0034] In some embodiments, the preparation method further comprises: after the micro-arc oxidation is completed, first grinding and polishing, cleaning the obtained material, and then performing physical vapor deposition.

[0035] In some embodiments, the preparation method further comprises: before etching and cleaning the substrate containing the micro-arc oxidation layer, cleaning it with an organic reagent such as petroleum ether, acetone, ethanol, etc. to remove oil stains on the surface.

[0036] A third object of the present invention is to provide an aluminum-based composite material, which is prepared by any of the methods described above.

[0037] The fourth object of the present invention is to provide the use of the aluminum-based composite material in preparing a moving plate or a stationary plate of a vehicle air-conditioning compressor. The moving plate and the stationary plate of the vehicle air-conditioning compressor prepared in this way have the advantages of low friction coefficient, strong load-bearing capacity, high COP (energy efficiency ratio), and good cooling and noise reduction effects.

[0038] Compared with the prior art, the present invention has at least the following beneficial effects:

[0039] (1) The present invention arranges the ta-C film on the micro-arc oxidation layer, which can significantly improve the hardness, wear resistance and corrosion resistance of the material and has high bonding strength; the chromium layer, tungsten carbide layer and carbon layer arranged in sequence in the ta-C film can make the ta-C film as a whole have a suitable hardness gradient, and the reasonable hardness transition can increase the bonding force between the three layers of the ta-C film, and increase the bonding force between the ta-C film as a whole and the micro-arc oxidation layer, and can also improve the toughness of the composite material;

[0040] (2) The aluminum-based composite material provided by the present invention has good corrosion resistance. The ta-C film can seal the tiny holes on the surface of the micro-arc oxidation layer, preventing the corrosive medium from entering through the holes and causing the ceramic film to fall off, thereby increasing the corrosion resistance of the material;

[0041] (3) The aluminum-based composite material provided by the present invention has good deformation resistance, which makes it not easy to deform and fail under high-speed and heavy-load conditions. It is particularly suitable for the preparation of components and equipment for high-speed and heavy-load conditions. The moving plate and static plate of the automotive air-conditioning compressor prepared by using it have the advantages of low friction coefficient, strong load-bearing capacity, and high COP (energy efficiency ratio). BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 is a friction coefficient diagram of the aluminum-based composite material prepared in Example 1 of the present invention;

[0044] Figure 2 is a cross-sectional electron microscope image of the aluminum-based composite material prepared in Example 2 of the present invention;

[0045] Figure 3 is a photograph of the thickness of the micro-arc oxidation layer formed in Example 3 of the present invention;

[0046] Figure 4 is a friction coefficient diagram of the aluminum-based composite material prepared in Comparative Example 1 of the present invention;

[0047] Figure 5 is a scanning electron microscope image of the micro-arc oxidation layer prepared in Comparative Example 1;

[0048] Figure 6is a surface hardness diagram of the aluminum-based composite material in Example 2 and Comparative Example 2 of the present invention;

[0049] Figure 7 A vehicle air-conditioning compressor turbine is prepared using the aluminum-based composite material in Example 1 of the present invention. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0051] Unless otherwise specified, the raw materials and reagents used in the present invention are all commercially available.

[0052] The test method of the friction and wear life in the specific embodiment of the present invention is: using the UMT-Tribolab multifunctional friction and wear tester to test the friction and wear life of the aluminum-based composite material in the atmospheric environment. The alumina ball and the test sample friction pair were subjected to reciprocating sliding motion with a sliding frequency of 5 Hz, a load of 5 N, an ambient temperature of (27±3)°C, a relative humidity of (75±5)%, and an experimental time of 30 min.

[0053] The bonding strength of aluminum-based composite materials is measured using the Step 300NHT3 nanoindentation method. The bonding strength rating method is to apply a controllable load on the coating surface, press the indenter into the film, measure the indentation depth in real time, and judge the coating bonding strength level by observing the cracks at the edge of the indentation. The specific steps are as follows:

[0054] The conical indenter of the Rockwell hardness tester (cone angle is 120°, and the radius of the apex is 0.2mm) is pressed into the coating surface under a certain test pressure. After 6 seconds, the pressure is released. The indenter will press a conical depression (indentation) on the surface of the sample. Observe the coating condition at the edge of the indentation and compare it with the crack judgment standard to determine the level of coating adhesion. The rating standards are divided into HF0~HF6.

[0055] The method for measuring the bearing capacity of aluminum-based composite materials is: under a high load (contact stress>1GP) applied to the aluminum alloy surface, observe the ease with which the film is prone to fall off. If the film is not removed, it means that the bearing capacity is good, otherwise it means that the bearing capacity is poor.

[0056] Example 1

[0057] In this embodiment, the surface of a 6061 aluminum alloy substrate is subjected to composite treatment by the following method to prepare an aluminum-based composite material. The specific steps are as follows:

[0058] 1. Pre-treat the surface of the aluminum alloy and polish it with 300#, 600#, 800#, 1000#, and 2000# fine sandpaper to remove surface dirt;

[0059] 2. Perform micro-arc oxidation treatment on the pretreated aluminum alloy: take the aluminum alloy as the anode and the stainless steel as the cathode, place the cathode and the anode together in a silicate electrolyte at a temperature of 20°C, the electrolyte uses deionized water as a solvent and contains 20g / L sodium silicate, 2g / L potassium hydroxide, 2g / L sodium metavanadate and 2g / L sodium dodecyl sulfate; select constant voltage mode for micro-arc oxidation, set the positive voltage to 500V, the negative voltage to 30V, the frequency to 400Hz, the duty cycle to 10%, and the oxidation time to 10min to form a micro-arc oxidation layer on the surface of the aluminum alloy;

[0060] 3. After the above micro-arc oxidation is completed, the obtained composite material is polished; and then washed with alcohol and deionized water in turn, and dried at room temperature for standby use;

[0061] 4. Use PI series coating equipment to deposit ta-C thin film, including the following steps:

[0062] (4-1) Before deposition, the surface of the aluminum alloy material containing the micro-arc oxidation layer was pretreated by scrubbing it in petroleum ether to remove surface oil stains, then ultrasonically cleaning it in acetone for 30 minutes, then ultrasonically cleaning it in anhydrous ethanol for 15 minutes, and finally drying it in a clean vacuum furnace;

[0063] (4-2) Using the PI series coating equipment manufactured by Anhui Chunyuan with a curved tube electromagnetic filtration system, the ta-C film was deposited. The material processed in step 4-1 was placed in a vacuum chamber, the chamber door was closed, and the vacuum was evacuated and heated to a vacuum degree of less than 2×10 -3 Pa, the temperature reaches 130℃, and it is etched and cleaned under the bias condition of -750V to remove dust and other impurities attached to the surface. The etching time is 80min;

[0064] (4-3) After etching is completed, Ar gas is introduced and the molecular pump speed is adjusted to control the pressure of the vacuum chamber to ≤ 1Pa; open the Cr target (the purity of the Cr target is 99.9%) to deposit the chromium layer for 160 min, close the Cr target; open the WC target to deposit the tungsten carbide layer for 350 min; after the tungsten carbide layer is deposited, adjust the Ar gas flow rate to control the deposition pressure at 0.8Pa, and adjust the temperature in the chamber to 30°C. When the vacuum degree is 1.5×10-3 Pa, the multi-arc current is set to 100A, the bias voltage is -760V, the graphite target is turned on to deposit the carbon layer, and the deposition time is 800min; after the deposition is completed, the protective gas argon is filled into the cavity, and the gas is released to atmospheric pressure. The cavity is opened and the furnace is taken out, and a ta-C film composed of a chromium layer, a tungsten carbide layer, and a carbon layer is formed on the surface of the micro-arc oxidation layer, thereby obtaining an aluminum-based composite material.

[0065] The thickness of the micro-arc oxidation layer formed in this embodiment is 15 μm, the thickness of the chromium layer is 600 nm, the thickness of the tungsten carbide layer is 100 nm, and the thickness of the carbon layer is 1.2 μm.

[0066] Figure 1 This is a graph of the friction coefficient of the aluminum-based composite material prepared in Example 1.

[0067] Example 2

[0068] In this embodiment, the surface of the 2024 aluminum alloy substrate is composite treated by the following method to prepare an aluminum-based composite material. The specific steps are as follows:

[0069] 1. Pre-treat the surface of the aluminum alloy and polish it with 300#, 600#, 800#, 1000#, and 2000# fine sandpaper to remove surface dirt;

[0070] 2. The pretreated aluminum alloy was subjected to micro-arc oxidation treatment: the aluminum alloy was used as an anode and the stainless steel was used as a cathode. The cathode and the anode were placed together in an electrolyte at a temperature of 50° C. The electrolyte used deionized water as a solvent and contained 25 g / L of sodium silicate, 4 g / L of potassium hydroxide, 4 g / L of sodium metavanadate and 3 g / L of sodium dodecyl sulfate. The micro-arc oxidation selected a constant voltage mode, set the positive voltage to 525 V, the negative voltage to 70 V, the frequency to 500 Hz, the duty cycle to 20%, and the oxidation time to 30 min to form a micro-arc oxidation layer on the surface of the aluminum alloy.

[0071] 3. After the above micro-arc oxidation is completed, the obtained composite material is polished; and then washed with alcohol and deionized water in turn, and dried at room temperature for standby use;

[0072] 4. Use PI series coating equipment to deposit ta-C thin film, including the following steps:

[0073] (4-1) Before deposition, the surface of the aluminum alloy material containing the micro-arc oxidation layer was pretreated by scrubbing it in petroleum ether to remove surface oil stains, then ultrasonically cleaning it in acetone for 30 minutes, then ultrasonically cleaning it in anhydrous ethanol for 15 minutes, and finally drying it in a clean vacuum furnace;

[0074] (4-2) Using the PI series coating equipment manufactured by Anhui Chunyuan with a curved tube electromagnetic filtration system, the ta-C film was deposited. The material processed in step 4-1 was placed in a vacuum chamber, the chamber door was closed, and the vacuum was evacuated and heated to a vacuum degree of 1×10 -3 Pa, the temperature reaches 150 ° C, and it is etched and cleaned under the bias condition of -800 V to remove dust and other impurities attached to the surface. The etching time is 90 minutes;

[0075] (4-3) After the etching was completed, Ar gas was introduced and the molecular pump speed was adjusted to control the pressure of the vacuum chamber at 0.8 Pa. The Cr target (the purity of the Cr target was 99.9%) was turned on to deposit the chromium layer for 175 min, and the Cr target was turned off. The WC target was turned on to deposit the tungsten carbide layer for 400 min. After the tungsten carbide layer was deposited, the Ar gas flow rate was adjusted to control the deposition pressure at 1.2 Pa, and the temperature in the chamber was adjusted to 140 °C. When the vacuum degree was 2.8×10 -3 Pa, the multi-arc current is set to 112A, the bias voltage is -850V, the graphite target is turned on to deposit the carbon layer, and the deposition time is 1400min; after the deposition is completed, Ar gas is filled into the cavity, and the gas is released to atmospheric pressure. The cavity is opened and the furnace is taken out, and a ta-C film composed of a chromium layer, a tungsten carbide layer, and a carbon layer is formed on the surface of the micro-arc oxidation layer, thereby obtaining an aluminum-based composite material.

[0076] The thickness of the micro-arc oxidation layer formed in this embodiment is 20 μm, the thickness of the chromium layer is 660 nm, the thickness of the tungsten carbide layer is 153 nm, and the thickness of the carbon layer is 3.3 μm. Figure 2 This is an electron microscope image of the cross section of the aluminum-based composite material prepared in Example 2, showing the thickness of each layer, where the ta-C film is about 4.2 μm.

[0077] Example 3

[0078] In this embodiment, the surface of the 7075 aluminum alloy substrate is composite treated by the following method to prepare an aluminum-based composite material. The specific steps are as follows:

[0079] 1. Pre-treat the surface of the aluminum alloy and polish it with 300#, 600#, 800#, 1000#, and 2000# fine sandpaper to remove surface dirt;

[0080] 2. Perform micro-arc oxidation on the pretreated aluminum alloy: use the aluminum alloy as an anode and stainless steel as a cathode, place the cathode and the anode together in an electrolyte at a temperature of 70°C, the electrolyte uses deionized water as a solvent and contains 30 g / L of sodium silicate, 5 g / L of potassium hydroxide, 5 g / L of sodium metavanadate and 3 g / L of sodium dodecyl sulfate; select constant voltage mode for micro-arc oxidation, set the positive voltage to 550 V, the negative voltage to 100 V, the frequency to 600 Hz, the duty cycle to 30%, and the oxidation time to 50 min to form a micro-arc oxidation layer on the surface of the aluminum alloy;

[0081] 3. After the above micro-arc oxidation is completed, the obtained composite material is polished; and then washed with alcohol and deionized water in turn, and dried at room temperature for standby use;

[0082] 4. Use PI series coating equipment to deposit ta-C thin film, including the following steps:

[0083] (4-1) Before deposition, the surface of the aluminum alloy material containing the micro-arc oxidation layer was pretreated by scrubbing it in petroleum ether to remove surface oil stains, then ultrasonically cleaning it in acetone for 30 minutes, then ultrasonically cleaning it in anhydrous ethanol for 15 minutes, and finally drying it in a clean vacuum furnace;

[0084] (4-2) Using the PI series coating equipment manufactured by Anhui Chunyuan with a curved tube electromagnetic filtration system, the ta-C film was deposited. The material processed in step 4-1 was placed in a vacuum chamber, the chamber door was closed, and the vacuum was evacuated and heated to a vacuum degree of 1.5×10 -3 pa, the temperature reaches 160℃, and it is etched and cleaned under the bias condition of -900V to remove dust and other impurities attached to the surface. The etching time is 100min

[0085] (4-3) After the etching was completed, Ar gas was introduced and the molecular pump speed was adjusted to control the pressure of the vacuum chamber at 0.9 Pa. The Cr target (the purity of the Cr target was 99.9%) was turned on to deposit the chromium layer for 190 min, and the Cr target was turned off. The WC target was turned on to deposit the tungsten carbide layer for 440 min. After the tungsten carbide layer was deposited, the Ar gas flow rate was adjusted to control the deposition pressure at 0.3 Pa, and the temperature in the chamber was adjusted to 350 °C. When the vacuum degree was 8×10 -4 Pa, the multi-arc current is set to 115A, the bias voltage is -900V, the graphite target is turned on to deposit the carbon layer, and the deposition time is 1000min; after the deposition is completed, Ar gas is filled into the cavity, and the gas is released to atmospheric pressure. The cavity is opened and the furnace is taken out, and a ta-C film composed of a chromium layer, a tungsten carbide layer, and a carbon layer is formed on the surface of the micro-arc oxidation layer, thereby obtaining an aluminum-based composite material.

[0086] The thickness of the micro-arc oxidation layer formed in this embodiment is 21 μm, the thickness of the chromium layer is 700 nm, the thickness of the tungsten carbide layer is 230 nm, and the thickness of the carbon layer is 2.1 μm. Figure 3 This is a photo of the thickness of the micro-arc oxidation layer in the aluminum-based composite material prepared in this example.

[0087] Example 4

[0088] Example 4 is basically the same as Example 1, except that the electrolyte used in Example 4 is: the electrolyte uses deionized water as a solvent and contains 40 g / L of sodium silicate, 12 g / L of potassium hydroxide, 15 g / L of sodium metavanadate and 5 g / L of sodium dodecyl sulfate.

[0089] Example 5

[0090] The preparation method of Example 5 is basically the same as that of Example 1, with the only difference being that, in the aluminum-based composite material prepared in Example 5, the thickness of the micro-arc oxidation layer is 25 μm, the thickness of the chromium layer is 1000 nm, the thickness of the tungsten carbide layer is 500 nm, and the thickness of the carbon layer is 3.5 μm.

[0091] Comparative Example 1

[0092] The only difference between Comparative Example 1 and Example 1 is that the aluminum-based composite material provided in Comparative Example 1 has only a micro-arc oxidation layer, and the preparation method of the micro-arc oxidation layer is the same as that of Example 1.

[0093] Figure 4 This is a friction coefficient diagram of comparative example 1 in which only a micro-arc oxidation layer is formed on a 6061 substrate, and the friction coefficient is measured to be 0.45. Figure 5 This is a scanning electron microscope image of the surface morphology of the micro-arc oxidation film of Comparative Example 1.

[0094] Comparative Example 2

[0095] The only difference between Comparative Example 2 and Example 2 is that the aluminum-based composite material provided in Comparative Example 2 has only a micro-arc oxidation layer, and the preparation method of the micro-arc oxidation layer is the same as that of Example 2.

[0096] The hardness of Example 2 and Comparative Example 2 was measured by the continuous stiffness method using the MTS-Nano G200 nano-indentation test platform. Figure 6 It is shown that the hardness of Example 2 and Comparative Example 2 are 2546 HV and 948 HV respectively, indicating that the aluminum-based composite material structure of Example 2 can significantly improve the mechanical properties of the material.

[0097] Comparative Example 3

[0098] The difference between Comparative Example 3 and Example 1 is that the step of depositing the chromium layer is not performed in step (4-3) of Comparative Example 3, that is, the tungsten carbide layer and the carbon layer are directly deposited on the micro-arc oxidation layer in sequence. The rest is the same as Example 1.

[0099] Comparative Example 4

[0100] The difference between Comparative Example 4 and Example 1 is that the step of depositing a tungsten carbide layer is not performed in step (4-3) of Comparative Example 4, that is, a chromium layer and a carbon layer are sequentially deposited on the micro-arc oxidation layer. The rest is the same as Example 1.

[0101] Comparative Example 5

[0102] The difference between Comparative Example 5 and Example 1 is that the step of depositing a carbon layer is not performed in step (4-3) of Comparative Example 5, that is, a chromium layer and a tungsten carbide layer are sequentially deposited on the micro-arc oxidation layer. The rest is the same as Example 1.

[0103] Comparative Example 6

[0104] The only difference between Comparative Example 6 and Example 1 is that the micro-arc oxidation is not performed, and the ta-C film is directly deposited on the 6061 aluminum alloy substrate, and the rest is the same as Example 1. It is found that when the ta-C film is directly deposited on the aluminum alloy surface, since the aluminum alloy material is very soft, and the ta-C film deposited by PVD is relatively thin, it is not enough to support the performance of the film layer under high-speed and heavy-load conditions, so the substrate is easily deformed and failed, indicating that the micro-arc oxidation layer and the ta-C film provided in the composite material can jointly improve the performance of the parts prepared by the composite material, and effectively avoid the failure of the aluminum alloy parts under high-speed and heavy-load conditions.

[0105] Comparative Example 7

[0106] The only difference between Comparative Example 7 and Example 1 is that the micro-arc oxidation technology is not used, and an anodizing method is used to form an oxide layer on the aluminum substrate, and then the ta-C film is prepared by the same method as Example 1. The specific steps of preparing the oxide layer by anodizing refer to "Li Ruocan, Duan Tigang et al.: Effects of anodized film and micro-arc oxidation film on seawater corrosion and mechanical properties of 5A06 aluminum alloy".

[0107] It is found that compared with the anodic oxidation method, the micro-arc oxidation method can form a ceramic layer of tens or hundreds of microns on the metal surface. This ceramic layer not only overcomes the defect of the thin oxide film formed by anodic oxidation, but also has obvious improvements and enhancements in corrosion resistance, wear resistance, electrical insulation and decorative properties. The former is used for decoration, and the latter is more suitable for bearing functions. For example, the aluminum-based composite material provided by the present invention is particularly suitable for preparing a compressor turbine for an automotive air conditioner. Figure 7 This is a photo of a vehicle air-conditioning compressor turbine made of the aluminum-based composite material of Example 1.

[0108] The relevant properties of the aluminum-based composite materials obtained in the above embodiments and comparative examples were tested, and the test results are shown in Table 1.

[0109] Table 1 Related properties of aluminum-based composite materials obtained in the embodiments of the present invention and comparative examples

[0110]

[0111]

[0112] The present invention adopts a surface composite treatment method combining micro-arc oxidation and physical vapor deposition, uses micro-arc oxidation to prepare an oxide layer, and uses arc ion plating to prepare a ta-C film on its surface. The obtained composite material has the characteristics of high hardness, high bonding strength, and low wear, and also has the surface structure improvement of the micro-arc oxidation substrate, which greatly improves the surface performance of the aluminum-based substrate, thereby effectively improving the comprehensive performance and service life of the substrate.

[0113] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0114] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0115] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. An aluminum-based composite material, characterized in that: include: A substrate, wherein the material of the substrate includes aluminum or aluminum alloy; A micro-arc oxidation layer is disposed on the surface of the substrate, and the micro-arc oxidation layer is prepared by a micro-arc oxidation method; A ta-C film is arranged on the surface of the micro-arc oxidation layer. The ta-C film is made by physical vapor deposition technology and comprises a chromium layer, a tungsten carbide layer and a carbon layer which are arranged in sequence in a direction away from the micro-arc oxidation layer.

2. The aluminum alloy composite material according to claim 1, characterized in that: The thickness ratio of the micro-arc oxidation layer to the ta-C film is 15-25:2.9-5; and / or, the thickness ratio of the chromium layer, the tungsten carbide layer and the carbon layer is 600-1000:100-500:1200-3500; And / or, the thickness of the micro-arc oxidation layer is 15-25 μm, the thickness of the ta-C film is 2.9-5 μm, wherein the thickness of the chromium layer in the ta-C film is 600-1000 nm, the thickness of the tungsten carbide layer is 100-500 nm, and the thickness of the carbon layer is 1.2-3.5 μm; and / or, the carbon layer is a hydrogen-free carbon layer; And / or, the material of the micro-arc oxidation layer includes alumina ceramics.

3. A method for preparing an aluminum-based composite material, characterized in that: include: Providing a substrate, wherein the material of the substrate includes aluminum or an aluminum alloy; Forming a micro-arc oxidation layer on the surface of the substrate by a micro-arc oxidation method; A chromium layer, a tungsten carbide layer and a carbon layer are sequentially deposited on the surface of the micro-arc oxidation layer by adopting a physical vapor deposition technology to form a ta-C film, thereby obtaining an aluminum-based composite material.

4. The preparation method according to claim 3, characterized in that: The micro-arc oxidation method specifically includes: using the substrate as an anode, placing it together with a cathode in an electrolyte containing 20-40 g / L silicate, and performing micro-arc oxidation treatment in a constant voltage mode; wherein the positive voltage is 500-550 V, the negative voltage is 30-100 V, the frequency is 400-600 Hz, and the duty cycle is 10-30%.

5. The preparation method according to claim 4, characterized in that: The micro-arc oxidation treatment time is 10 to 50 minutes; And / or, the temperature of the electrolyte is 20-70°C; And / or, the silicate includes one or a combination of multiple of sodium silicate, sodium metasilicate, potassium silicate, iron silicate, magnesium silicate and calcium silicate; And / or, the electrolyte further comprises 2-12 g / L of an alkaline pH regulator, 2-15 g / L of a colorant and / or 2-5 g / L of a surfactant; preferably, the alkaline pH regulator comprises sodium hydroxide and / or potassium hydroxide, the colorant comprises one or more of sodium metavanadate, copper sulfate, and copper carbonate, and the surfactant comprises sodium dodecyl sulfate and / or sodium fluoride; And / or, the cathode is made of stainless steel.

6. The preparation method according to claim 3, characterized in that: Before depositing the ta-C film, the substrate containing the micro-arc oxidation layer is etched and cleaned, and the etching and cleaning comprises: placing the substrate containing the micro-arc oxidation layer in a physical vapor deposition reaction chamber, and -3 The etching and cleaning are carried out under the conditions of 0.27477 Pa, 130-160° C. temperature and -700--900 V bias voltage, and then the ta-C film is deposited.

7. The preparation method according to claim 3, characterized in that: The physical vapor deposition technology specifically includes: in an argon atmosphere with a gas pressure less than or equal to 1 Pa, using a chromium target and a tungsten carbide target to deposit a chromium layer and a tungsten carbide layer respectively, wherein the deposition time of the chromium layer is 60 to 190 minutes, and the deposition time of the tungsten carbide layer is 350 to 440 minutes; and / or, after the tungsten carbide layer is formed, the pressure of the argon atmosphere is adjusted to be less than or equal to 1.5 Pa and the vacuum degree is less than or equal to 3×10 -3 Pa, and adjust the temperature to 30-50° C., the multi-arc current to 100-115A, the bias voltage to -750--900V, and use a graphite target for deposition for 800-1500min to form the carbon layer on the tungsten carbide layer.

8. An aluminum-based composite material, characterized in that: It is prepared by the method described in any one of claims 3 to 7.

9. Use of the aluminum-based composite material according to claim 1, 2 or 8 in preparing a moving disc or a stationary disc of a vehicle air-conditioning compressor.

Citation Information

Patent Citations

  • Preparation method for composite layer of bearing and bearing with composite layer

    CN105970215A

  • Ta-C deposition coating method

    CN114481025A

  • High-wear-resistance protective composite coating on surface of valve and application of high-wear-resistance protective composite coating

    CN118272810A

  • A process for forming coatings on metallic surfaces

    SG157239A1

  • Amorphous carbon covered member

    US20010024737A1